Bilateral clear cell acanthoma of the areola and nipple: good response to topical corticosteroids - Elena González-Guerra; Jorge Ruiz Rodriguez; Alejandro Fueyo Casado; Alberto Conde Taboada; Jose Antonio Cortes Toro; Eduardo Lopez Bran (Sociedade Brasileira de Dermatologia, 2017)
Abstract: Clear cell acanthoma is a rare, epidermal tumor not common in the area of the nipples; indeed, the literature describes only 8 cases, all showing unilateral presentation. We here report the first case of bilateral clear cell acanthoma with good response to topical corticosteroids. Case report: A sixteen-year old girl presented with 2 excrescent, fleshy, and exudative tumor masses in both nipples and areola mammae. A biopsy was conducted and confirmed clear cell acanthoma histopathologically. Treatment with strong corticosteroids resulted in rapid improvement and resolution. After one year of follow-up, the patient developed atopic dermatitis. Discussion: We describe the first case of bilateral clear cell acanthoma localized in the nipple/areola that resolved with powerful corticosteroids, suggesting a reactive etiology of the lesion.